International multicenter comparative trial of transluminal EUS-guided biliary drainage via hepatogastrostomy vs. choledochoduodenostomy approaches - Khashab, Mouen A.; Messallam, Ahmed A.; Penas, Irene; Nakai, Yousuke; Modayil, Rani J.; De la Serna, Carlos; Hara, Kazuo; El Zein, Mohamad; Stavropoulos, Stavros N.; Perez-Miranda, Manuel; Kumbhari, Vivek; Ngamruengphong, Saowanee; Dhir, Vinay K.; Park, Do Hyun (Endoscopy International Open, 2016)
Background and study aims: Endoscopic ultrasound-guided biliary drainage (EUS-BD) can be performed entirely transgastrically (hepatogastrostomy/EUS-HG) or transduodenally (choledochoduodenostomy/EUS-CDS). It is unknown how both techniques compare. The aims of this study were to compare efficacy and safety of both techniques and identify predictors of adverse events.Patients and methods: Consecutive jaundiced patients with distal malignant biliary obstruction who underwent EUS-BD at multiple international centers were included. Technical/clinical success, adverse events, stent complications, and survival were assessed. Results: A total of 121 patients underwent EUS-BD (CDS 60, HG 61). Technical success was achieved in 112 (92.56 %) patients (EUS-CDS 93.3 %, EUS-HG 91.8 %, P = 0.75). Clinical success was attained in 85.5 % of patients who underwent EUS-CDS group as compared to 82.1 % of patients who underwent EUS-HG (P = 0.64). Adverse events occurred more commonly in the EUS-HG group (19.67 % vs. 13.3 %, P = 0.37). Both plastic stenting (OR 4.95, 95 %CI 1.41 – 17.38, P = 0.01) and use of non-coaxial electrocautery (OR 3.95, 95 %CI 1.16 – 13.40, P = 0.03) were independently associated with adverse events. Length of hospital stay was significantly shorter in the CDS group (5.6 days vs. 12.7 days, P < 0.001). Mean follow-up duration was 151 ± 159 days. The 1-year stent patency probability was greater in the EUS-CDS group [0.98 (95 %CI 0.76 – 0.96) vs 0.60 (95 %CI 0.35 – 0.78)] but overall patency was not significantly different. There was no difference in median survival times between the groups (P = 0.36) Conclusions: Both EUS-CDS and EUS-HG are effective and safe techniques for the treatment of distal biliary obstruction after failed ERCP. However, CDS is associated with shorter hospital stay, improved stent patency, and fewer procedure- and stent-related complications. Metallic stents should be placed whenever feasible and non-coaxial electrocautery should be avoided when possible as plastic stenting and non-coaxial electrocautery were independently associated with occurrence of adverse events.